IDENTIFIKASI FORMALIN DAN BORAKS PADA PRODUK BAKSO DI KECAMATAN BANYUWANGI - Putra, Irvan (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2020)
High nutrition foods are highly perishable, therefore it needs special handling from spoiling quickly, one of which is the addition of food additive for producing desired food. The total number of banned food additive are 19 type of additive, one of which is formalin and borax. Based on data by BPOM in 2010, top rank of food that contained formalin and borax from 786 of sample including slot deposit 5000 meatball, fish and tofu. Banyuwangi district was selected for meatball sampling represent the population due to the highest location of sales of meatball. Research parameters used were analysis of physical characteristic, formalin and borax. Theresearch objective was to know the physical characteristic of meatball contained formalin and borax in Banyuwangi District. Sampling method used purposive sampling. Formalin test with the combination of ET test-kit and KMnO4 method showed negatives while using KMnO4 method showed positive of formalin with no change in color. The result of rapid testkit and bead test was negatives of borax.